Regulatory and Conceptual Review Related to the Medical-legal Opinion on Violent Injuries in Colombia (2019)
Purpose: Currently, the technological medical advance in diagnosis, treatment and rehabilitation requires that the parameters for medical-legal assessment of the individuals who turn to the Colombian justice sector be reviewed. To this end, regulatory and conceptual data on non-fatal injuries are collected, especially in relation to repair times and the factors affecting them. Period covered, origin and types of publications: The period covered for the conceptual analysis is between 2006 and 2018, with articles compiled from PubMed and Science Direct and no preference as to origin. A related national legislative review is carried out. Point of view: Although the determination of injury repair was established as a starting point for medical- legal opinions, its variability and the impact of new technologies on health deserves resignifying how these times are measured on an individual basis. Conclusions: It is essential to advance research studies in our population groups in order to obtain information for the forensic sector.